2017
DOI: 10.4103/0970-2113.197120
|View full text |Cite
|
Sign up to set email alerts
|

The minimum volume of pleural fluid required to diagnose malignant pleural effusion: A retrospective study

Abstract: Background:Pleural fluid cytology is a quick and accurate method to diagnose malignant pleural effusions. The optimal volume of fluid for cytological analysis has not yet been identified, and clinical recommendation based on some published clinical experiences has been to send large volumes of fluid for cytological analysis. A quality improvement initiative at our institution was conducted to determine the volume of fluid sufficient for a diagnosis of malignant pleural effusion.Materials and Methods:The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Wu et al evaluated 74 patients whose effusions were divided to three volumes as 25, 50, 125 mL. Although detection rate of malignant cells increased from 88% to 100% with increased volume, the findings were not statistically significant to suggest one group over the other 18 . Thomas et al concluded in their analysis that the sensitivity did not increase after 50 mL, 19 and Abouzgheib suggested 25 to 50 mL would be sufficient for high sensitivity 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al evaluated 74 patients whose effusions were divided to three volumes as 25, 50, 125 mL. Although detection rate of malignant cells increased from 88% to 100% with increased volume, the findings were not statistically significant to suggest one group over the other 18 . Thomas et al concluded in their analysis that the sensitivity did not increase after 50 mL, 19 and Abouzgheib suggested 25 to 50 mL would be sufficient for high sensitivity 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors which influence the diagnostic yield include specimen handling, volume of fluid submitted and extent of pleural involvement . As for the minimal volume necessary for proper fluid interpretation, there is relatively strong evidence in the literature that a minimal range volume of around 50‐75 mL should be adopted, to diminish potential false negatives and optimise the test sensitivity . Determination of volume submitted for examination was beyond the scope of the current study, but clinicians at our hospital tend to send all aspirated volume for analysis in the laboratory and therefore this should not be a factor contributing for our non‐diagnostic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although the systematic review identified 3 prospective cohort studies [104][105][106] and 4 retrospective cohort studies [107][108][109][110] that all reported on minimum volume of fluid required for a diagnosis, the expert panel believed there was too much heterogeneity within the identified studies upon which to base an evidence-based statement. Additionally, no study reported on an upper limit of fluid.…”
Section: Pleural Effusions: Considerations For Malignancymentioning
confidence: 99%